The rule of claw - Brindley, John, 1954- (Minneapolis, MN : Carolrhoda Books, 2009)
Ash and her friends live in a future where they are the only human teenagers left, but when Ash is kidnapped and becomes a pawn in a power struggle among the formidable Raptors who captured her, she begins to reconsider her own humanity.
Young Adult
Keywords: Good and evil -- Juvenile fiction; Kidnapping -- Juvenile fiction; Good and evil -- Fiction; Kidnapping -- Fiction; Science fiction; Good and evil -- Fiction; Kidnapping -- Fiction; Science fiction